WATERING OF SYNTHETIC OILS FOR AIRCRAFT - N. E. Syrojedov; S. A. Galko; F. E. Sharykin; N. A. Muratkhanov (Научный вестник МГТУ ГА, 2016)
The article presents the analysis of aviation synthetic oils watering, as one of the most important factors affecting the engine wear of aircraft equipment, as well as the quality of oils during storage and use. Cause-and-effect relationship between the change of operational properties of synthetic aviation oils and their watering, as well as the influence of oil watering on flight safety are disclosed.